New Azo Dyes-Based Mg Complex Pigments for Optimizing the Anti-Corrosion Efficiency of Zinc-Pigmented Epoxy Ester Organic Coatings - Kohl, Miroslav; Alafid, Fouzy Ramadan Ali; Boštíková, Karolína; Bouška, Marek; Krejčová, Anna; Svoboda, Jan; Šlang, Stanislav; Michalíčková, Ludmila; Kalendová, Andréa; Hrdina, Radim; Burgert, Ladislav; Schmidová, Eva; et al. (MDPI, 2023)
This work addresses the possibilities of using synthesized novel magnesium complex dyes in zinc pigmented organic coatings based on epoxyester resin to reduce the zinc content in these coatings while maintaining or increasing the anticorrosive efficiency of them. The magnesium complexes Mg-Dye-I (C34H26MgN8O6), Mg-Dye-II (C26H19MgN3O5), Mg-Dye-III (C17H10MgN2O3), and Mg-Dye-IV (C25H18MgN4O6) with a series of azo carboxylate ligands were prepared from the diazo-coupling reaction of anthranilic acid with 5-methyl-2-phenyl-3-pyrazolone (Dye I; C17H14N4O3), anthranilic acid with naphthol AS-PH (Dye II; C26H21N3O5), anthranilic acid with 2-naphthol (Dye III; C17H12N2O3), and 2-amino-5-nitrophenol with naphthol AS-PH (Dye IV; C25H20N4O6). The synthesized novel magnesium complex dyes were characterized by analytical methods. Model coatings containing these dyes at pigment volume concentrations (PVCs) = 1, 3, 5 and 10% and zinc at a ratio of pigment volume concentration/critical pigment volume concentration (PVC/CPVC) = 0.60 were formulated to study the inhibitory properties of the individual synthesized magnesium complex dyes. Model coatings containing inorganic pigments (MgO and Ca-Mg-HPO4) at PVCs = 1%, 3%, 5% and 10% and zinc at PVC/CPVC = 0.60 were also formulated. The coating pigmented only by zinc at PVC/CPVC = 0.60 was prepared as a standard organic coating. Corrosion resistance was also evaluated by potentiodynamic polarization studies and electrochemical impedance spectroscopy. The properties of organic coatings were also tested using other standardized and derived corrosion tests. In addition, the mechanical properties of the studied organic coatings were determined using standard tests. The aim of the work was to verify the possible synergistic efficiency of novel magnesium complex dyes by improving the mechanical, anti-corrosion, and chemical properties of zinc pigmented organic coatings.
Nové Mg komplexní pigmenty na bázi azobarviv pro optimalizaci antikorozní účinnosti zinku pigmentovaných epoxyeserových organických povlaků
Keywords: magnesium complex; azo dyes; coating; corrosion; anticorrosion efficiency; hořčíkový komplex; azobarvivo; povlak; koroze; antikorozní účinnost